DFP-Induced Status Epilepticus Severity in Mixed-Sex Cohorts of Adult Rats Housed in the Same Room: Behavioral and EEG Comparisons - Rao, Nikhil S.; Meyer, Christina; Vasanthi, Suraj S.; Massey, Nyzil; Samidurai, Manikandan; Gage, Meghan; Putra, Marson; Almanza, Aida N.; Wachter, Logan; Thippeswamy, Thimmasettappa (Frontiers in Cell and Developmental Biology, 2022)
Sex is a biological variable in experimental models. In our previous diisopropylfluorophosphate (DFP) studies, female rats required a higher dose of DFP to achieve a somewhat similar severity of status epilepticus (SE) as males. In those studies, male and female rats were bought separately from the same vendor, housed in different rooms, and the DFP used was from different batches. We had also shown that surgery for epidural electrodes implantation reduces the threshold for SE. Our recent study in the soman (GD) model using a mixed-sex cohort of rats housed individually but in the same room showed that females achieved significantly higher SE severity than males for the same dose of GD. In this study, we demonstrate that housing the mixed-sex cohorts in the same room and treating them with DFP (4mg/kg, s.c.) from the same pool, though from different batches, yielded reproducible SE severity in both sexes and both telemetry (surgery) and non-telemetry (non-surgery) groups. We conducted experiments in four mixed-sex cohorts of adult Sprague-Dawley rats. In females, the surgery for implanting the telemetry devices reduced the latency to convulsive seizure (CS) and increased SE severity compared to non-telemetry females. However, there were no sex differences in latency or SE severity within telemetry or non-telemetry groups. Once animals reached CS stage ≥3, they remained in CS stage in both sexes until midazolam was administered. Midazolam (3mg/kg, i.m.) treatment one-hour post-DFP significantly reduced epileptiform spikes in both sexes. The mortality was only 2% in 24h. Irrespective of sex or stage of estrous cycle or surgery, the animals had continuous convulsive SE for ~ 40 minutes. In telemetry rats, electrographic changes correlated with behavioral seizures. However, there was a significant difference in SE severity and the latency between directly-observed behavioral CS and EEG-based CS quantification in both sexes. Overall, these results suggest that housing both sexes in the same room and treating with DFP in a mixed-sex cohort from the same pool of reagents will minimize variability in SE severity. Such rigorous experiments will yield better outcomes while testing disease-modifying agents in epilepsy models.